Logistyka jako narzędzie równoważenia rozwoju - Skowrońska, Agnieszka (Logistics as a tool to sustain development, 2007)
This paper aims at pointing to logistics as crucial tools that can both inerease competitivenes and speed up, or undoubtedly facilitate, development sustainability. The author tries to suport the aforementioned statement by pointing out that: concepts, methods, and techniąues used in logistics facilitate forming of sustainability systems in relation to the assumed objectives of development and wildlife mechanisms; delivery chains based on the logistic environmental imperative facilitate accomplishment of the assumptions of sustainable development; logistic centres thanks to supporting dematerialization of logistic process of co-operating business entities and intelligent structurization, facilitate accomplishment of the principles of the ecoeffectiveness code.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 483-494